THE MODEL OF STUDENTS‘ SAVING EMPOWERMENT MANAGEMENT - Amini Amini; Syamsu Yurnita; Hasnidar Hasnidar (State Islamic University of North Sumatra Indonesia, 2019)
This research has been carried out to help overcome the problems of financial management in schools / madrasas, especially in private schools / madrasas related to financial governance that already apply in the institution. The model referred to in this study is a management model of empowering student savings funds. the trial model that was applied in MIS Mutiara located on Jl. Teak No. 125 Sei Delivering Deli Serdang Regency. Based on the results of the study found a model of student empowerment management empowerment, namely the principal of MIS Mutiara, making policies in schools / madrasas on the existence of suggested daily student savings activities, socialized to students' parents, parents welcomed positively, class teachers collect savings every day from their students, then class teachers deposit it with the school treasurer, the school treasurer deposits it to the Muhammadiyah BMT every day through the account of the head of MIS Mutiara, the Muhammadiyah BMT manages it and each month prepares money for teacher salaries of Rp. 6,000,000, which is for as many as 6 teachers each month. the advantage of the management model of student savings empowerment conducted at MIS Mutiara is that teachers can get payday (every 2nd). While the drawbacks need to be very careful in financial management, so that if there is misuse is vulnerable to the confidence of parents of students in sending their children to school again. Keywords: Model of Management, Empowerment, Students’ Saving